2006
DOI: 10.2337/diabetes.55.01.06.db05-0894
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Induced Reactive Oxygen Species Cause Apoptosis of Podocytes and Podocyte Depletion at the Onset of Diabetic Nephropathy

Abstract: Diabetic nephropathy is the most common cause of endstage renal disease in the U.S. Recent studies demonstrate that loss of podocytes is an early feature of diabetic nephropathy that predicts its progressive course. Cause and consequences of podocyte loss during early diabetic nephropathy remain poorly understood. Here, we demonstrate that podocyte apoptosis increased sharply with onset of hyperglycemia in Ins2Akita (Akita) mice with type 1 diabetes and Lepr db/db (db/db) mice with obesity and type 2 diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
421
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 963 publications
(494 citation statements)
references
References 53 publications
26
421
1
1
Order By: Relevance
“…It has been reported that increased glucose concentration generates intracellular ROS, which activates p38, resulting in apoptosis in podocytes (Susztak et al 2006). Further, high glucoseinduced phosphorylation of p38 in human endothelial cells leads to cell death (Nakagami et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that increased glucose concentration generates intracellular ROS, which activates p38, resulting in apoptosis in podocytes (Susztak et al 2006). Further, high glucoseinduced phosphorylation of p38 in human endothelial cells leads to cell death (Nakagami et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Endpoint micro-and macro-vascular complications such as nephropathy, retinopathy and cardiovascular disease are associated with increased morbidity and mortality in diabetic patients. Diabetic nephropathy is progressive and irreversible and is characterised by glomerular hyperfiltration, epithelial hypertrophy, microalbuminuria, glomerulus basement membrane thickening and proteinuria and is the leading cause of end-stage renal disease worldwide (4)(5)(6)(7)(8). Intensive glycaemic control and interventions with angiotensin converting enzyme (ACE)-inhibitors are intended to delay disease progression but are not curative (9).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in renal function may lead to electrolytes retention and imbalance hence accelerating the development of cardiovascular disease complications (16,17). Metformin is commonly administered as a firstline drug in the treatment of type 2 diabetes as it suppresses hepatic gluconeogenesis, decreases fatty acid oxidation and increases peripheral insulin sensitivity, leading to improved glucose uptake in the skeletal muscles and adipose tissues (7,(18)(19)(20). These effects of metformin are mediated by its activation of 5'-AMP-activated protein kinase (AMPK), (a known master energy sensor that restores cellular energy balance) and also by inhibition of complex 1 of the mitochondrial ETC leading to reduced mitochondrial ROS production (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…The podocytes are insulin-sensitive cells (Coward et al 2005, Welsh et al 2010) that contract to limit diuresis, fluxing nutrients into the urine for the primary purpose of nutrient retention and post-prandial utilisation. Unfortunately, the podocyte is a terminally differentiated cell with limited capabilities to regenerate and proliferate following injury, therefore reduced podocyte density is argued to be a crucial determinant in the development and progression of DN (Pagtalunan et al 1997, Susztak et al 2006. The induction of ER stress has been elegantly reviewed in primary glomerular diseases (Dickhout & Krepinsky 2009).…”
Section: Er Stress-mediated Glomerular Injurymentioning
confidence: 99%